In-situ Compressive Strength Assessment of Reinforced Concrete Structures - Al-Neshawy Fahim; Wallenius Antti; Jouni Punkki Prof. (Nordic Concrete Research)
The strength of existing concrete structures can be evaluated and quantified where necessary with non-destructive and destructive testing methods. The aim is to determine the structural adequacy of existing concrete structures and to test the integrity of the concrete structures based on their strength evaluation.